2019
DOI: 10.4236/aim.2019.912066
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of <i>Psidium guajava</i> Leaf Extract against Selected Pathogenic Bacteria

Abstract: This study has been embarked upon due to increased resistance of bacteria to many already synthesized drugs and the high price of the orthodox medicines in the market, the antimicrobial effect of Psidium guajava leaf extracts against selected drug-resistant bacteria will help to reduce the overdependence on orthodox or synthetic drugs which greater population of the society cannot afford due to economic/financial restriction. Ethanolic and aqueous extracts of Psidium guajava were assayed for antibacterial acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
(5 reference statements)
1
6
0
1
Order By: Relevance
“…This corroborates the findings of Sushmita et al [2]. Ngene et al [20] equally reported that Gram positive organisms exhibited smaller MIC when exposed to extracts of Psidium guajava than those of Gram negative organisms. The Minimum Bactericidal Concentration showed that the leaves and stem extracts of the plant can kill the isolates at 12.5 -50 mg/ml.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This corroborates the findings of Sushmita et al [2]. Ngene et al [20] equally reported that Gram positive organisms exhibited smaller MIC when exposed to extracts of Psidium guajava than those of Gram negative organisms. The Minimum Bactericidal Concentration showed that the leaves and stem extracts of the plant can kill the isolates at 12.5 -50 mg/ml.…”
Section: Discussionsupporting
confidence: 92%
“…Ibe and Maduagwu [4] and Nwanneka et al [19] also reported the efficacy of Alkaloids as anti-imalaria, anticancer and antiasthma. Ngene et al [20] reported that tannins are effective in treating intestinal disorders such as diarrhea and dysentery.…”
Section: Discussionmentioning
confidence: 99%
“…26 After 24 hrs, broth was filtered using double Whatmans filter paper (qualitative paper with grade 597). 29 The filtrate was dried on a rotary evaporator and the left thick paste-like substance was stored at 4°C in glass vials for further studies. Further, mycelium collected was washed with warm water to ensure no residue of solvent and nutrient medium is left.…”
Section: Metabolite Extraction and Fermentationmentioning
confidence: 99%
“…The World Health Organization (WHO) has categorized more than 20,000 medicinal plant species providing treatment for diseases such as, ulcers, pneumonia diarrhoea, colds, bronchitis and diseases of the respiratory tracts. The use of plant extracts and phyto-products is gaining attention due to their availability, cost-effectiveness, proven nature of specificity, biodegradability, low toxicity, and minimum residual toxicity in the ecosystem [10].…”
Section: Introductionmentioning
confidence: 99%